Sustaining belief: the church of Worcester from c. 870 to c. 1100 - Tinti, Francesca (Studies in early medieval Britain, 2010)
Sustaining belief through memory, land, and pastoral care -- Personnel : bishop and cathedral community -- Archival memory and record-keeping -- Land, lordship, and justice -- Ecclesiastical organization and pastoral care